Contrasting lexical biases in bilingual English–Mandarin speech : verb-biased mothers, but noun-biased toddlers - Setoh, Peipei (2021)
Is noun dominance in early lexical acquisition a widespread or a language-specific phenomenon? Thirty Singaporean bilingual English–Mandarin learning toddlers and their mothers were observed in a mother-child play interaction. For both English and Mandarin, toddlers’ speech and reported vocabulary contained more nouns than verbs across book reading and toy playing. In contrast, their mothers’ speech contained more verbs than nouns in both English and Mandarin but differed depending on the context of the interaction. Although toddlers demonstrated a noun bias for both languages, the noun bias was more pronounced in English than in Mandarin. Together, these findings support early noun dominance as a widespread phenomenon in the lexical acquisition debate but also provide evidence that language specificity also plays a minor role in children’s early lexical development.